Effects of Impedance Control on Haptic Perception of Object Properties: A Qualitative and Quantitative Approach - Takeru Hashimoto; Shigeo Yoshida; Takuji Narumi (IEEE Access)
Previous research on haptic feedback in virtual reality often relies on single quantitative measures, potentially overlooking the diversity of user perceptions regarding sensory experiences. To address this gap, we conducted user interviews and thematic analysis to uncover how users perceive physical properties when interacting with varying levels of motion impedance, such as changes in inertia, viscosity, and elasticity. Through evaluation experiments using the semantic differential method, we identified four key perceptual dimensions—size, viscosity, weight, and flexibility—related to changes in impedance. Furthermore, we analyzed and examined how each impedance parameter influences these perceptual dimensions. Our findings offer a framework for designing haptic feedback systems that can better capture a variety of user perceptions, leading to more personalized and immersive virtual reality experiences.